Endoscopic ultrasound-guided celiac ganglia neurolysis vs. celiac plexus neurolysis: a randomized multicenter trial - Doi, S.; Yasuda, I.; Kawakami, H.; Hayashi, T.; Hisai, H.; Irisawa, A.; Mukai, T.; Katanuma, A.; Kubota, K.; Ohnishi, T.; Ryozawa, S.; Hara, K.; Itoi, T.; Hanada, K.; Yamao, K. (Endoscopy, 2013)
Background and study aims: No prospective comparison of endoscopic ultrasonography-guided direct celiac ganglia neurolysis (EUS – CGN) vs. EUS-guided celiac plexus neurolysis (EUS – CPN) has been reported. The aim of the current study was to compare the effectiveness of EUS – CGN and EUS – CPN in providing pain relief from upper abdominal cancer pain in a multicenter randomized controlled trial.Patients and methods: Patients with upper abdominal cancer pain were randomly assigned to treatment using either EUS – CGN or EUS – CPN. Evaluation was performed at Day 7 postoperatively using a pain scale of 0 to 10. Patients for whom pain decreased to ≤ 3 were considered to have a positive response, and those experiencing a decrease in pain to ≤ 1 were considered to be completely responsive. Comparison between the two groups was performed using intention-to-treat analysis. The primary endpoint was the difference in treatment response rates between EUS – CGN and EUS – CPN at postoperative Day 7. Secondary endpoints included differences in complete response rates, pain scores, duration of pain relief, and incidence of adverse effects.Results: A total of 34 patients were assigned to each group. Visualization of ganglia was possible in 30 cases (88 %) in the EUS – CGN group. The positive response rate was significantly higher in the EUS – CGN group (73.5 %) than in the EUS – CPN group (45.5 %; P = 0.026). The complete response rate was also significantly higher in the EUS – CGN group (50.0 %) than in the EUS – CPN group (18.2 %; P = 0.010). There was no difference in adverse events or duration of pain relief between the two groups.Conclusions: EUS – CGN is significantly superior to conventional EUS – CPN in cancer pain relief. Clinical trial registration: http://www.umin.ac.jp/ctr/index.htm (ID: UMIN-000002536)